Hierarchical Assembly of Model Cell Surfaces: Synthesis of Mucin Mimetic Polymers and their Display on Supported Bilayers - Rabuka, David (2007)
Molecular level analysis of cell surface phenomena could benefit from model systems comprising structurally-defined components. Here we present the first step toward bottom-up assembly of model cell surfaces – the synthesis of mucin mimetics and their incorporation into artificial membranes. Natural mucins are densely glycosylated O-linked glycoproteins that serve numerous functions on cell surfaces. Their large size and extensive glycosylation makes the synthesis of these biopolymers impractical. We designed synthetically tractable glycosylated polymers that possess rod-like extended conformations similar to natural mucins. The glycosylated polymers were end-functionalized with lipid groups and embedded into supported lipid bilayers where they interact with protein receptors in a structure-dependent manner. Furthermore, their dynamic behavior in synthetic membranes mirrored that of natural biomolecules. This system provides a unique framework with which to study the behavior of mucin-like macromolecules in a controlled, cell surface-mimetic environment.